Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Nasabah BPJS Kesehatan di Puskesmas Ujung Kubu Kabupaten Batu Bara - Suri Sakinah Handayani; Tri Inda Fadhila Rahma; Juliana Nasution (LPPM Universitas Labuhanbatu, 2023)
The purpose of this study was to determine the quality of services and facilities for BPJS health customer satisfaction at the Ujung Kubu Health Center in Batu Bara Regency, using a questionnaire data collection technique distributed to respondents using the Probability Sampling method with the Simple Random Sampling technique using Slovin flats, with a sample size of 74 respondents. Service quality has a positive and significant effect on customer satisfaction at the Ujung Kubu Health Center in Batu Bara Regency. This can be seen in the t test table in the Standardizes Coefficients column, which proves that service quality has a 32.7% value on customer satisfaction. This value proves that service quality has an effect on customer satisfaction. The facilities at the Ujung Kubu Health Center in Batu Bara Regency have no problems because the more complete and adequate the facilities provided, the more customer satisfaction increases. So by looking at the t test table in the column Standardiez coefficients. This proves that facilities have an effect on customer satisfaction of 27.7%, this value proves that facilities have an effect on customer satisfaction. Based on the simultaneous test between service quality and facilities on customer satisfaction there is a significant influence. This condition was supported by the questionnaires distributed by the researcher to the respondents where most of the respondents answered that they agreed to all statements. However, there was a decrease in the percentage in the statement that after seeking further information the customer wanted to have BPJS at the Ujung Kubu Health Center in Batu Bara district. For the results of the determination test, the magnitude of R2 is 0.260, which means that 26% of the customer satisfaction variable is influenced by the variable quality of service and facilities, while the remaining 74% is influenced by other variables not examined by researchers.Â